Organization Of Correctional Education And Upbringing In Special Schools For Deaf And Weak Hearing Children - Feruza Khakimbekovna Salomova (Euro Asian Journal Publishing, 2024)
the article presents important corrective tasks in the process of teaching hearing perception and pronunciation, information on the formation and development of the skills of perception and reproduction of oral speech in children with hearing impairment.
Keywords: child with hearing impairment; correction; tactile-motor